Analisis Dampak Ekonomi Festival Budaya Terhadap Perekonomian Daerah: (Studi Kasus Perayaan Hut Kabupaten Bulungan) - Mita Anriyani; Aslan A (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the economic impact of cultural festivals on the regional economy, using the anniversary celebration of Bulungan Regency as a case study. This research employs a descriptive qualitative approach supported by simple quantitative data obtained through a Likert-scale questionnaire. The study involved 30 respondents consisting of MSME (Micro, Small, and Medium Enterprise) owners, local community members, and other relevant stakeholders. Data were collected through interviews, observations, questionnaires, and documentation, and were analyzed using an interactive analysis model consisting of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the cultural festival has a significant economic impact on the regional economy. Directly, the festival increased the number of customers, business revenues, and profits, with the level of respondent agreement exceeding 80%. In addition, the festival contributed to market expansion, improved business promotion and reputation, and created opportunities for new business partnerships and networks. The indirect impacts included increased business capacity, product innovation, and the strengthening of the local economy through the multiplier effect. In the long term, the cultural festival was found to support business sustainability, increase demand for local products, and strengthen the identity and attractiveness of the region. However, several aspects still need improvement, including facilities, venue management, and event organization, so that the economic impacts generated can be optimized. Therefore, the cultural festival held as part of the anniversary celebration of Bulungan Regency serves not only as a ceremonial event but also as a strategic instrument for regional economic development based on local potential.